Reviewing the notion of progress in the quest for sustainability: the example of Chinese architecture - Li, Mengbi (Journal of Architecture and Urbanism, 2019)
Progress is a frequently admired concept in modern societies, yet defining and achieving it requires renewed consideration in the context of sustainability and low-carbon living. This paper suggests that in China, the modern concept of progress came as a result of certain historical events in the late nineteenth and early twentieth centuries when the country was trapped in crisis. This concept was useful in stimulating society at that time and contributed to the rapid development that followed, but whether it can still meet the new challenges of today’s China is questionable. Focusing on the discipline of architecture, this paper suggests that now is the time for a critical rethink of the concept of progress. There are valuable notions to be found in China’s history when addressing these challenges.